(untitled) (LACCEI, 2024)
Obesity is a constantly growing problem since 2016, with an impact in the last 2 years where most people lived a very sedentary life that affected their metabolism and led them to be overweight, in addition to the direct relationship that exists between people with a low socioeconomic level and the prevalence of overweight, due to problems of low education and poverty. For this, an application research with a quantitative approach was carried out, with an experimental group of 33 students and another control group of 33 students to contrast the experimental group, which has not been significantly affected by external factors. Finally, it was obtained as results that the BMI of adolescents improved by an average of 2%. In the same way, knowledge retention is optimal, since initial knowledge was improved by an average of 60%.